Four newly recorded species of the family Coleophoridae (Lepidoptera: Gelechioidea) from Korea - Koo, Jun-Mo; Cho, Soowon (Zootaxa, 2026)
We report four species of the family Coleophoridae (Gelechioidea) for the first time in Korea: Coleophora citrarga Meyrick, 1934; C. helgada (Anikin, 2005); C. obscuripalpella Kanerva, 1941; and C. varilimosipennella Li & Zheng, 2000. Among these, the host plant of C. varilimosipennella is reported here for the first time. The diagnostic characteristics and redescriptions of each of the four species are provided. With this report, a total of 47 coleophorid species are known from Korea. In addition, a revised Korean vernacular name for Coleophora montaniella Oku & Kusunoki, 2018 is proposed to avoid confusion due to name duplication.